The Participation toward on Corporate Social Responsibilities of the guesthouse business in the Luang Prabang city Luang Prabang Province - duangsavath, touyphoutthasone; HOONGSENGPHA, Soudtida; Phommachack, thongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objectives of this research were to study the operating conditions of guesthouse business in the Luang Prabang city, to study The Participation toward on Corporate Social Responsibilities of the guesthouse business in the Luang Prabang city Luang Prabang Province and to analyze the Corporate Social Responsibilities participation influences the operation of the guesthouse business in the Luang Prabang city Luang Prabang Province. The research was conducted by using a questionnaire as an instrument for collecting data from 124 Guesthouse Entrepreneurs/executives in the Luang Prabang city, Luang Prabang Province. The Cronbach alpha reliability coefficient was 0.968. The statistics used for data analysis were frequency, percentage, mean, standard deviation, multiple regression analysis. The results found that: In terms of success in the operation of the guesthouse business, it was found that the overall the business has a high level of success consisted of marketing, internal Management, productsand Financial Perspective. Participation toward Corporate Social Responsibilities of the guesthouse business in Luang Prabang city. Overall, the Guesthouse business had been involved in social responsibility at a higher level. With a lot of responsibility towards on Good corporate governance of the organization, the Conducting business with fairness in the organization, the corporate consumer responsibility, the Environmental carrying and the participating development in community and social. The Social responsibility in terms of environmental responsibility and the participating development in community and social had influences the financial /returns of the Guesthouse business, the participating development in community and social had influences in the Marketing of the guesthouse business, social responsibility in terms of the Conducting business with fairness in the organization and the participating development in community and social had influences in the management and Productsof the guesthouse business in the Luang Prabang city.